Representasi Klaim Merakyat dalam Iklan TVC “Coblos Nomor 3, Menangkan Rakyat” Pasangan Ganjar-Ma’fud dalam Iklan Pemilihan Presiden 2024 - Muhammad Furqon Dwi Nur Rohmad; Fajar Junaedi (Universitas Muhammadiyah Klaten, 2026)
This study aims to analyze the representation of the populist claim in the political advertisement of the Ganjar-Ma’fud duo, titled